(untitled) (Asian Journal of Social Science Studies, 2018)
Over the past 30 years of renovation, the development of the socialist-oriented market economy has built up a team of good ethic and competent medical personnel who have devoted their lives to serving and caring health of people. However, the implementation and improvement of medical ethics in the past years has also been challenging such as harassment, negligence, hidden fees, low quality of examination and treatment, disease, etc., reducing the belief of the people for the noble duty "save life" of the medical staff. Therefore, enhancing medical ethics for health care workers is becoming more and more pressing. This is a problematic situation where in the process of building a modern Vietnamese medicine that meets the requirements of development, must continue to study in order to have a scientific basis to set the direction and solution for further raising medical ethics for this team.